The Cambridge companion to Bob Dylan (Cambridge companions to American studies, 2009)
"A towering figure in American culture and a global twentieth-century icon, Bob Dylan has been at the centre of American life for over forty years. The Cambridge Companion to Bob Dylan brings fresh insights into the imposing range of Dylan's creative output. The first Part approaches Dylan's output thematically, tracing the evolution of Dylan's writing and his engagement with American popular music, religion, politics, fame, and his work as a songwriter and performer. Essays in Part II analyse his landmark albums to examine the consummate artistry of Dylan's most accomplished studio releases. As a writer Dylan has courageously chronicled and interpreted many of the cultural upheavals in America since World War II. This book will be invaluable both as a guide for students of Dylan and twentieth-century culture, and for his fans, providing a set of new perspectives on a much-loved writer and composer."--BOOK JACKET.